Development and Validation of Analytical Method for Simultaneous Estimation of Formoterol Fumarate Dihydrate and Fluticasone Propionate from Bulk and Dry Powder Inhaler Formulation - Godge, Rahul K; Satpute, Soniya S; Sagar, Magar M (Journal of Drug Delivery and Therapeutics, 2019)
A method was developed and validated for analysis of Formoterol Fumarate and Fluticasone Propionate in dry powder inhaler formulations. Separation was achieved on a HiQ Sil C18HS, 250×4.6 mm, 5 µm column using a mobile phase consisting of Acetonitrile: 0.01 M Ammonium Dihydrogen Phosphate solution (80:20 %v/v) at a flow rate of 1ml/min PDA detection at 215.0 nm. This method is validated according to ICH guidelines, which include linearity, precision, accuracy, specificity, robustness. The result obtained were within the acceptance criteria as per ICH guidelines. Keywords: formoterol fumarate dihydrate, fluticasone propionate, buffer, HPLC.